1996
DOI: 10.1002/(sici)1097-4644(199610)63:1<94::aid-jcb8>3.0.co;2-v
|View full text |Cite
|
Sign up to set email alerts
|

Differential and multiple binding of signal transducing molecules to the ITAMs of the TCR-ζ chain

Abstract: A biotin-streptavidin-based technique was developed for high affinity, unidirectional, and specific immobilization of synthetic peptides to a solid phase. Biotinylated 23-mer carboxamide peptides corresponding to the three immunoreceptor tyrosine-based activation motifs (ITAMs) of the T cell antigen receptor associated zeta-chain (TCR-zeta) in their bis-, mono-, or unphosphorylated forms were used to study the binding of cellular proteins from human Jurkat T cells to these signal transduction motifs. The prote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
18
0
1

Year Published

1996
1996
2016
2016

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 48 publications
(22 citation statements)
references
References 30 publications
1
18
0
1
Order By: Relevance
“…Peptide Binding Assays-ITAM-containing biotinylated 23-mer carboxamide peptides (Table I) were prepared as described (13). Each peptide (10 g/ml in 50 l of 50 mM Tris pH 7.5, 100 mM NaCl (TBS) was incubated with 60 liters of streptavidin-agarose beads (Sigma) with rotation for 1 h at 4°C.…”
Section: Methodsmentioning
confidence: 99%
“…Peptide Binding Assays-ITAM-containing biotinylated 23-mer carboxamide peptides (Table I) were prepared as described (13). Each peptide (10 g/ml in 50 l of 50 mM Tris pH 7.5, 100 mM NaCl (TBS) was incubated with 60 liters of streptavidin-agarose beads (Sigma) with rotation for 1 h at 4°C.…”
Section: Methodsmentioning
confidence: 99%
“…Experiments performed in T-cell lines indicated that the cytoplasmic domains of the CD31 and z subunits were independently capable of providing activating signals similar to that of the intact TCR complex (Irving and Weiss 1991;Letourneur and Klausner 1992;Wegener et al 1992) and suggested that TCR ITAMs are functionally redundant but additive with respect to signaling responses (Irving et al 1993). In other studies, the binding of potential effector proteins including ZAP-70, Shc, PI3K( p85), Grb2, Fyn, and Ras-GAP to the TCR ITAMs was analyzed using synthetic phosphorylated peptides containing individual ITAM sequences Osman et al 1996;Zenner et al 1996). Only one of the three studies compared binding to all 6 TCR ITAM sequences (z1, z2, z3, CD32g, 2d, and 21) (Osman et al 1996).…”
Section: Function Of Individual Tcr Chains and Itamsmentioning
confidence: 99%
“…However, Lck has also been linked to negative signaling through activation-induced cell death after ligation of the TCR with partial agonists [15], and we and others have shown, that the Ras-MAPK, or a Ga11-dependent PLCb-mediated pathway may be triggered in the absence of Lck [16][17][18], ZAP-70 [19] or LAT phosphorylation [20]. This indicates that one or more alternative pathways of Tcell activation exist, and it has been proposed that a Grb2-SOS complex can be recruited to incompletely phosphorylated CD3f [20][21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%